3-D fatigue crack study in the rail - Chen, Xiaoyong (2018)
Fatigue crack growth is one of the major cause of catastrophic accident in the railway system, it will destroy the whole structure and lead to derailment. Hence it is essential to study the fatigue crack growth behavior in the rail, to ensure the structural reliability of the railway system thus ensures a high safety level in the daily operation There were many researches had been made on investigating the stress intensity factor of cracks in the rails, however the study about fatigue crack study on the railway subjected to multiple cyclic loading is not common. As a full scale of experimental setup is time consuming and costly, therefore, a simulation software ABAQUS 6.14 was used to simulate the fatigue crack behavior in the railway. In this project, Extended Finite Element Method (XFEM) was adapted for numerical simulations. In this report, 42 models were simulated, to find out the different factors that affect the fatigue crack propagation behavior.